2003
DOI: 10.1111/j.1469-7793.2003.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ageing on the electrical and mechanical properties of human soleus motor units activated by the H reflex and M wave

Abstract: This study was designed to investigate the effect of ageing on the mechanical and electromyographic (EMG) characteristics of the soleus motor units (MUs) activated by the maximal Hoffmann reflex (H max ) and by the direct muscle compound action potential (M max ). Eleven young (mean age 25 ± 4 years) and ten elderly (mean age 73 ± 5 years) males took part in this investigation. The senior group presented lower amplitudes of M max (_57 %, P < 0.001) and H max (_68 %, P < 0.001) waves compared to the younger pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 51 publications
3
30
0
5
Order By: Relevance
“…F ) with the variability reported in the current study similar to that previously found in older individuals (Scaglioni et al . ). It is possible, however, that the lack of association in these cyclists could also be because the ageing signal is indeed less, or is masked by the more constrained age range (55–79 years) studied here as opposed to those studying wider age ranges including young individuals (20–80 years).…”
Section: Discussionmentioning
confidence: 97%
“…F ) with the variability reported in the current study similar to that previously found in older individuals (Scaglioni et al . ). It is possible, however, that the lack of association in these cyclists could also be because the ageing signal is indeed less, or is masked by the more constrained age range (55–79 years) studied here as opposed to those studying wider age ranges including young individuals (20–80 years).…”
Section: Discussionmentioning
confidence: 97%
“…In the present investigation, we recorded the M‐wave evoked concomitantly with the H‐reflex and calculated the M at‐ H max / M max ratio, which is used to control the stability of recording conditions (Schieppati, ). The SOL M at‐ H max represented 11–17% of the SOL M max in all the experimental conditions, in agreement with earlier values reported in the literature (Maffiuletti et al ., ; Scaglioni et al ., ; Grospretre & Martin, ; Cattagni et al ., ). The lack of change in M at‐ H max / M max ratio through the three types of pressure application demonstrated the stability of conditions during H‐reflex recordings.…”
Section: Discussionmentioning
confidence: 99%
“…This increased vulnerability to falls could be a consequence of aging-related effects on sensorimotor function. Changes such as decreased muscle strength and power,27 longer latencies, lower magnitudes, and increased burst durations of postural responses,28 and attenuated neural excitability and weaker reflex torques,29 have been implicated in heightened fall risk with aging. These deteriorations may alter older adults’ regular movement patterns or weaken their reactions,9, 30 causing deficiencies in controlling slip severity, resisting limb collapse, and re-establishing stability,15, 31, 32 leading to more falls, regardless of task.…”
Section: Discussionmentioning
confidence: 99%